Letramento literário na escola: uma proposta curricular para os anos finais do ensino fundamental - Sousa, Hildenia Onias de (2023)
This research with a qualitative approach and bibliographic procedures aimed at the elaboration of a curricular proposal for teaching literature in the final years of elementary school, focusing on literary literacy. To this end, the route outlined consists of a bibliographic review on the teaching of literature through the years of 2011-2020, a reading of the BNCC as a guiding document for school curricula, as well as an approach on curriculum and literature. The theoretical contribution on literary literacy is based on the Brazilian meaning taken in the studies of Paulino (2004; 2005; 2010) and Cosson (2006; 2020; 2021; 2022). Regarding the concepts of curriculum, authors such as Sacristán (2013), Saviani (2016), Santomé (2013), and others were sought. For theoretical conceptions about literature, Candido (1972; 2004), Culler (1999), Eagleton (2003), Aguiar e Silva (2007), Compagnon (2014) and Jouve (2010; 2019) were used to discuss the conceptualization attempts and reach the conception adopted by literary literacy. Following this route, the curricular proposal was elaborated consisting of the organization of stages that favor the construction of the readers' profile, the organization of the readers' communities, the reading practices, the mediation strategies, the formation of a literary shelf and mobilization of knowledge. Thus, understanding that the school must practice curricular justice (SANTOMÉ, 2013), literary literacy is an alternative to contribute for this to happen through the organization of times-spaces for reading, of libraries that have a good literary collection which allows the handling of texts and continuous activities that are planned and systematized to be developed inside and outside the school, respecting the specificities of the community of readers. In this sense, it is expected that the school will contribute to broaden the notion of literature beyond the texts written and legitimized as literary, bringing other texts, whether from the oral tradition, the Internet, cinema, the mass media, with the aim of the student to understand that literature participates in these texts and they also participate in literature. From this perspective, this research brings contributions in the sense of offering a critical analysis of the material collected on the teaching of literature, reflections on the curriculum, as well as a curricular proposal for teaching literature with a focus on literary literacy, with the possibility of contributing to the inclusion of diversity in the school curriculum.